Hubungan Antara Kohesivitas Keluarga dan Self Esteem pada Remaja - Fendi Krisna Rusdiana (Personifikasi: Jurnal Ilmu Psikologi, 2020)
ABSTRACT This study aims to examine the relationship between family cohesiveness and self-esteem in adolescents. The population in this study were students of a private junior high school in Surabaya. The samples taken were students in two class VII and students in two class VIII totaling 110 students. This research uses correlational quantitative method. Sampling using stratified random sampling technique. The data were collected using a family cohesiveness scale and a self-esteem scale. The data analysis technique used is the product moment correlation. The results of data analysis showed a correlation value (r) of 0.411 and a significance value (p) of 0.002. This suggests that there is a relationship between family cohesiveness and self-esteem in adolescents.  ABSTRAKPenelitian ini bertujuan untuk menguji hubungan antara kohesivitas keluarga dengan self-esteem pada remaja. Populasi pada penelitian ini adalah siswa salah satu SMP swasta di Surabaya. Sampel yang diambil adalah siswa di dua kelas VII dan siswa di dua kelas VIII berjumlah 110 siswa. Penelitian ini menggunakan metode kuantitatif korelasional. Pengambilan sampel menggunakan teknik stratified random sampling. Pengumpulan data menggunakan skala kohesivitas keluarga dan skala self-esteem. Teknik analisis data yang digunakan adalah korelasi product moment. Hasil analisis data menunjukkan nilai korelasi (r) sebesar 0,411 dan nilai signifikansi (p) sebesar 0,002. Hal ini menyatakan bahwa terdapat hubungan antara kohesivitas keluarga dengan self-esteem pada remaja.